Brazil : The Role of the Tobacco Control Program in Curbing Smoking - Iglesias, Roberto; Jha, Prabhat; Pinto, Márcia; Costa e Silva, Vera Luiza da; Godinho, Joana (World Bank, Washington, DC, 2012)
Available evidence indicates that there was a significant decline in smoking in Brazil between 1989 and 2006. About two decades ago, the government launched a tobacco control program, with a marked acceleration of efforts since 1990, focusing on non-price interventions such as bans on advertising, restrictions on smoking in public places, and other activities. Although the Brazil tobacco control program is considered one of the most comprehensive in the developing world, no formal evaluation has been carried out. A recent study assessed the smoking situation in Brazil and the role of the tobacco control program, and compared it to experience in other countries. The study assessed key trends in smoking rates and lung cancer in Brazil, and reviewed price and non-price interventions. A discussion of fiscal instruments and smuggling is also included in the report. The study found that a 10 percent increase in smoking restrictions (legal and other restrictions), will reduce consumption by 2.3 percent in the long term, a 10 percent price increase will reduce consumption by about 4.8 percent in the long-term. The study shows that an increase of 72 percent in the cigarette specific tax will increase prices by about 14 percent, decrease consumption per adult 7 percent, and increase fiscal income from tobacco by 60 percent. Econometric studies, such as those included in this report, may contribute to appraise policy impact on public health. Analyzes of the costs of smoking to households the health system, labor market, and the economy, as well as the impact of price and tax increases on smoking habits, and on the burden of disease, will provide useful contributions for further development of public policy in this area.